The Use of Flashcards and Numbered Heads Together Technique to Improve Students' Vocabulary Knowledge - Aji, Rudi Wibowo; Farida, Alief Noor (ELT Forum: Journal of English Language Teaching, 2019)
This quasi experimental study aims to find out the effectiveness of the use of Flashcards collaborated with Numbered Heads Together Technique compared to the use of only Flashcards to improve seventh grade students of SMP Negeri 1 Tulis, Batang vocabulary knowledge. The data was obtained through pre-test and post-test. Conventional change score data analysis showed that the control group achieved better vocabulary knowledge improvement result with 3.42 compare to 2.66 improvement result of experimental group. Likewise, the data analysis using process-oriented change score by Frost (2014) also favour the control group with 22% improvement than the experimental group with 19% improvement. Thus, Flashcards is more effective than Flashcards collaborated with Numbered Heads Together Technique to improve students’ vocabulary knowledge. Keywords: flashcards; Numbered Heads Together; vocabulary knowledge; quasi experimental research